Efficient Technology for Introduction Catch-Crops Into Soil (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
A sharp decrease in the number of cattle in Latvia has essentially affected the possibilities to introduce organic fertilizers into soil. A solution of this problem may be growing catch-crop plants. The purpose of this study is to clarify the factors, technologies and machinery ensuring good and widespread introduction of catch-crops (winter rape, spring rape, red clover, fallow) without their previous shredding. It is found that unthreaded catch- crop plants may be qualitatively introduced into soil using a combined aggregate by orienting them in the direction of the movement of the aggregate and inclining them towards the surface of the field (rolling with the roller) and simultaneously plugging in with a plough which has a disk knife in front of each body to cut the inclined plants and a greater width (50 cm), and adjustable mouldboard curvature having improved skimmers to avoid clogging and to turn over the arable strips in a better way and to ensure more complete plugging of plants into soil. The technology of introducing catch-crops into soil without previous disintegration has been tested in practice and it is an environment-saving means of preserving and raising soil fertility. It is economically efficient in comparison with the introduction of previously shredded plants presently used on farms. It is possible to raise the introduction quality of unthreaded plants (also long-stalked ones) to 96-98%. Optimization the technology and the plough completion allow save labor – 1.4-1.8 men h ha-1, fuel 6-8 kg ha-1 and financial means 5,60-7,20 Ls ha-1.